Challenges in Translating Moroccan Oral Tradition: The Case of Folktales from the Region of Abdelghaya Souahel - Ouachan, Abdelmajid; Sadik , Maliki Moulay; Fadoua , El Heziti (International Journal of Language and Literary Studies, 2024)
This study examines some challenges encountered in translating Moroccan folktales from the region of Abdelghaya Souahel into English, focusing on linguistic and cultural problems. In this regard, Moroccan oral tradition, including folktales, plays a pivotal role in preserving cultural identity and transmitting community values. However, translating these narratives involves addressing dialect variation, cultural symbolism, structural differences, and some performative aspects that form an integral part of oral storytelling. Through a cultural and linguistic analysis of ten folktales collected from the region, this study identifies some specific translation challenges and proposes strategies to preserve the authenticity of the stories while making them accessible to a broader audience. By addressing these challenges, this study contributes to a broader discourse on the preservation and dissemination of cultural heritage through translation.